فرش القراءات القرآنية وأسراره البلاغية :‏‏ ‏‏دراسة وصفية تحليلية في ثلاثة أجزاء /‏ - Amirah Ahmad Zain (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This study deals with rhetorical nuances associated with the multiplicity of farsh (specific variance in certain verses) in the readings of the Qur'an within the scope of three ajzaa' namely the fourteenth to sixteenth. The researcher found that the variance in terms of farsh occurs in verbs, nouns as well as particles. The specific locations where farsh variance occurs were identified and the implicit reasons for its occurrence are analysed in the light of both the linguistic and situational contexts. Based on this study, the researcher arrived at a conclusion that there are specific points of signification that can be attributed to the variance and this highlights another dimension of the eloquence of the Holy Qur'an.